Nutritional Intake in Children with Functional Constipation in a Tertiary Care Hospital in Jakarta, Indonesia - Cindy Febrina; Gendis Sekarnegari Putri; Kitra Latuasan; Adrian Himawan Singgih; Diana Sunardi; Ariani Dewi Widodo (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background: Functional constipation affects 0.7–29.6% of children worldwide. Dietary factors, including carbohydrate, protein, fat, fiber and fluid intake, are known factors associated with constipation. Constipation impacts children's growth and psychosocial functioning. This study aims to assess macronutrients and fluid intake in children with functional constipation. Methods: A descriptive study was conducted at the Gastrohepatology Outpatient Clinic, Harapan Kita Mother & Children Hospital, from November to December 2025. Age, sex, nutritional status, and intake of carbohydrate, protein, fat, fiber, and fluid were assessed. Results: Thirty-one subjects were included. The majority were female (58.1%), aged 1–3 years (45.2%), with normal nutritional status (61.3%). Most subjects had lower energy intake than recommended (90.3%), while 12.9% had inadequate protein intake. More than half had adequate fat intake (58.1%) while only 32.3% met the carbohydrate target. Using the “age + 5” rule, the majority had fiber intakes below recommended values. Additionally, 90.3% had fluid intake below recommended levels. Conclusion: Children with functional constipation were predominantly young and female, and more than half had normal nutritional status; however, most did not meet recommended energy, carbohydrate, fiber, and fluid intake levels. These findings indicate that dietary intakes were frequently below recommended levels in this sample and underscore the need to strengthen public education regarding appropriate nutrition to support the prevention and management of constipation.